Longitudinal brain changes in MDD during emotional encoding: effects of presence and persistence of symptomatology. Issue 8 (6th June 2020) - Ai, Hui; Opmeer, Esther M.; Marsman, Jan-Bernard C.; Veltman, Dick J.; van der Wee, Nic J. A.; Aleman, André; van Tol, Marie-José
Abstract: Background: The importance of the hippocampus and amygdala for disrupted emotional memory formation in depression is well-recognized, but it remains unclear whether functional abnormalities are state-dependent and whether they are affected by the persistence of depressive symptoms. Methods: Thirty-nine patients with major depressive disorder and 28 healthy controls were included from the longitudinal functional magnetic resonance imaging (fMRI) sub-study of the Netherlands Study of Depression and Anxiety. Participants performed an emotional word-encoding and -recognition task during fMRI at baseline and 2-year follow-up measurement. At baseline, all patients were in a depressed state. We investigated state-dependency by relating changes in brain activation over time to changes in symptom severity. Furthermore, the effect of time spent with depressive symptoms in the 2-year interval was investigated. Results: Symptom change was linearly associated with higher activation over time of the left anterior hippocampus extending to the amygdala during positive and negative word-encoding. Especially during positive word encoding, this effect was driven by symptomatic improvement. There was no effect of time spent with depression in the 2-year interval on change in brain activation. Results were independent of medication- and psychotherapy-use. Conclusion: Using a longitudinal within-subjects design, we showed that hippocampal–amygdalar activation during emotional memory formation is related to depressive symptom severity but not persistence (i.e. time spent with depression or 'load'), suggesting functional activation patterns in depression are not subject to functional 'scarring' although this hypothesis awaits future replication.